Produção e caracterização de filmes biodegradáveis de isolado proteico de soja contendo micropartículas de óleo essencial de orégano - Paglione, Isabela dos Santos (2018)
Synthetic packaging is widely used in Brazil and worldwide, but it has the disadvantage of requiring a high degradation time and when not reused, it generates a problem of waste accumulation. An alternative would be the use of biodegradable packaging produced with biopolymers from renewable source such as soy protein isolate (SPI). SPI films allow the incorporation of bioactive compounds such as oregano essential oil (OEO). However, OEO is easily degraded during processing, and an alternative to preserve the bioactivity of this compound would be the microencapsulation. This study was divided in two stages. The first consisted of evaluating the effect of pH and concentration of SPI on the properties of SPI films using a central rotational compound design (DCCR). It was observed that at high pHs, tensile strength (RT) and elongation at break (ELO) of films were increased. Solubility (SOL) and color parameter L* were observed, with the lowest values of these variables being obtained at alkaline pH, far from the isoelectric point, in which denaturation of the soybean proteins occurred, allowing interaction between the chains and the formation of a compact structure. Considering the desirability function, to obtain a film with high RT and ELO and low SOL it is necessary to use 7.56% of SPI and to adjust the filmogenic solution to pH 10.54. The second step of this study consisted in microencapsulate the OEO by the ionic gelation technique and apply it in the formulation of SPI films. OEO was successfully microencapsulated by ionic gelation technique and presented spherical shape, mean diameter of 250 μm and encapsulation efficiency of 79.6%. The presence of free OEO decreased the RT and Young's modulus (MY), and increased SOL and these results may be related to the reduction of the polymer-polymer interaction, forming a less cohesive and weak structure. The addition of free OEO provided antimicrobial activity against S. aureus and E. coli, and this action decreased after 90 days of storage. The presence of microencapsulated oregano essential oil (OEOM) increased the RT and MY, decreased ELO and PVA of the films. It is believed that there was a good interaction between the film matrix and the OEO microparticles, resulting in the reinforcement of the polymer matrix. The microencapsulation of the oil protected the bioactive compounds present in the OEO during the production and drying of the films, allowing to obtain materials with antimicrobial properties.